2010
DOI: 10.1158/1055-9965.epi-09-1245
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Lymphedema after Breast Cancer Treatment

Abstract: Background: As cancer treatments evolve, it is important to reevaluate their effect on lymphedema risk in breast cancer survivors.Methods: A population-based random sample of 631 women from metropolitan Philadelphia, Pennsylvania, diagnosed with incident breast cancer in 1999 to 2001, was followed for 5 years. Risk factor information was obtained by questionnaire and medical record review. Lymphedema was assessed with a validated questionnaire. Using Cox proportional hazards models, we estimated the relative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 63 publications
5
121
3
1
Order By: Relevance
“…Chemotherapy has also been determined to be a significant risk factor for the development of lymphedema (12,23,26,27). In a study investigating the cosmetic results of breast cancer treatment, the patient group who underwent adjuvant chemotherapy was determined to have far more complications (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy has also been determined to be a significant risk factor for the development of lymphedema (12,23,26,27). In a study investigating the cosmetic results of breast cancer treatment, the patient group who underwent adjuvant chemotherapy was determined to have far more complications (26).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our findings revealed that chemotherapy was a significant risk factor. The exact mechanism is not known; however, one may speculate that those patients receiving chemotherapy may have received more aggressive treatment (27). There are also studies that have reported a lack of association between chemotherapy and lymphedema (1,23,28).…”
Section: Discussionmentioning
confidence: 99%
“…Well-defined risk factors for developing lymphedema include axillary lymph node dissection (ALND), [9][10][11][12][13][14][15] regional lymph node irradiation (RLNR), 8,[16][17][18][19] higher body mass index (BMI), and older age at diagnosis. 7,8,11,14,[20][21][22][23][24][25][26][27][28][29][30] It remains unclear why, among patients with similar demographic and treatment-related characteristics, some go on to develop lymphedema.…”
Section: Introductionmentioning
confidence: 99%
“…The number of lymph nodes removed was the only participant characteristic shown to have a statistically significant difference between attenders and non-attenders. Numerous research studies have concluded that lymph node removal is a key risk factor for developing breast cancer-related lymphedema [3,[17][18][19][20][21][22]. Since nonattenders had fewer lymph nodes removed, one may posit that a reason for their lack of compliance was that they did not feel they were at risk for lymphedema or in need of an OT lymphedema consult.…”
Section: Discussionmentioning
confidence: 99%